On the Emergence of the Castellieri Settlements and Possible Effects of Climatic Changes in the 2nd Millennium BC in the Adriatic Region - Anja Hellmuth Kramberger (Quaternary)
The fortified hilltop settlement of Monkodonja, located near Rovinj on the west coast of Istria, Croatia, provides insight into Bronze Age occupation and conflict in the Adriatic region. Established around 2000 BC, as evidenced by a series of C14 dates from human and animal bones, the settlement experienced significant construction phases, particularly in its defensive architecture. Its earliest fortifications, built with limestone blocks using dry-stone wall techniques, date to the 19th century BC, with major expansions in the 16th century BC, where the primary wall was doubled in width and reached over 3 m in thickness. Monkodonja’s architectural complexity, notably the West Gate and Acropolis fortifications, and certain types of artifacts reveal influences from southern regions such the eastern Aegean. However, the settlement appears to have met a violent end around the 15th century BC, suggested by destruction layers, widespread burning, and the presence of weapons such as a lance tip, bronze axe, and slingstones. Monkodonja’s destruction raises questions about broader military conflicts in the Adriatic region during this period. Possible causes could include localized warfare or connections to larger-scale disturbances. Research in Monkodonja is also significant in the context of the debate surrounding the emergence of the so-called Castellieri settlements in Istria at the beginning of the 2nd millennium BC. As early as the beginning of the 20th century, it was proposed that a migration of people to the Istrian peninsula brought this new settlement form and other influences, leading to a significant population increase. The appearance of the Castellieri settlement form coincides with a period marked by documented climatic changes and two major natural disasters in the form of volcanic eruptions.